World Economic Outlook, May 1992. (World Economic Outlook; World Economic Outlook, 1992)
This paper highlights that following a small decline in world output in 1991, growth will recover to about 1 1\2 percent in 1992 before gaining more momentum in 1993. There were signs of recovery in some of those industrial economies that have been in recession, but some other countries continued to show signs of weakness. Although the sluggishness of many cyclical indicators continues to highlight the downside risks to the short-term projections, there are several positive aspects of the current situation.